Academic Literacy Practices: The Language of Hedging in Indonesian EFL Students' Essays - Dewi, Rohmatul Fitriyah; Andania, Ruqoyyah Amilia; Tlonaen, Zuvyati Aryani (Inspiring: English Education Journal, 2024)
Writing academically and reading are parts of literacy that it is embedded in higher education. Therefore, it is important to assess how students’ ability can develop critical thinking regarding specific issues using hedging language. The purpose of this study was to evaluate students' critical thinking skills by looking at how effectively they hedgingly constructed their writings. Moreover, this study also explored the students' viewpoints about the use of hedging in their academic pursuits. This research employed a qualitative approach. The data was collected from students’ essays from the English Department in Surabaya and the results of a semi-structured interview with three students. Hyland (1998) identified eight categories of hedging, which were used in the text analysis. The study's findings demonstrate that students employed the majority of hedging strategies when writing their essays. However, the most used is modal auxiliaries, which focus more on the specific subject being taught and utilize a variety of tools to communicate their ideas. Moreover, it is found that different students provided varied reasons for employing hedging, such as reducing criticism, avoiding precision methods, or maintaining a particular writing style. Overall, the research underscores the multifaceted role of hedging in shaping both the content and perception of students' academic essays.